1997
DOI: 10.1042/bj3270577
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 is a binding protein on the HepG2 cell surface for tissue factor pathway inhibitor

Abstract: Tissue factor pathway inhibitor (TFPI) is a primary regulator of the initiation of blood coagulation. TFPI is internalized and degraded by HepG2 cells through the low-density-lipoprotein receptor-related protein (LRP) but also binds another molecule present on the cell surface at approx. 10-fold the abundance of LRP [Warshawsky, Broze and Schwartz (1994) Proc. Natl. Acad. Sci. U.S.A. 91, 6664-6668]. When HepG2 cells are washed with heparin or dextran sulphate, a substance that binds TFPI is removed from the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 33 publications
6
47
0
1
Order By: Relevance
“…Proteoglycan receptors that are known to bind TFPI-1 are the transmembrane-anchored ryudocan/syndecan 4 14 and the glycosyl phosphatidylinositol (GPI)-anchored glypican 3. 15 In a previous study, we found evidence that the primary anchoring of endogenous TFPI-1 on the surface of ECV304 cells is through a GPI linkage, 16 and similar conclusions were drawn from studies using primary human umbilical vein endothelial cells in culture. 17 The type of membrane anchoring influences the localization of cell surface receptors to specific areas of the cell membrane.…”
supporting
confidence: 48%
See 2 more Smart Citations
“…Proteoglycan receptors that are known to bind TFPI-1 are the transmembrane-anchored ryudocan/syndecan 4 14 and the glycosyl phosphatidylinositol (GPI)-anchored glypican 3. 15 In a previous study, we found evidence that the primary anchoring of endogenous TFPI-1 on the surface of ECV304 cells is through a GPI linkage, 16 and similar conclusions were drawn from studies using primary human umbilical vein endothelial cells in culture. 17 The type of membrane anchoring influences the localization of cell surface receptors to specific areas of the cell membrane.…”
supporting
confidence: 48%
“…ECV304 cells express members of the GPI-anchored glypican family of heparan-sulfated proteoglycans that likely associate with the detergent-insoluble membrane domains as a result of their specific membrane attachment. A previous study has demonstrated that the glypican 3 core protein binds specifically to immobilized TFPI-1, 15 and we find no significant displacement of the endogenous inhibitor from ECV304 cells on incubation with heparin. Clusters of negatively charged residues in glypican 1 and 3 are highly conserved 32 and may contribute to protein-protein interactions with basic regions of TFPI, resulting in high-affinity binding that is only Figure 3.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, endogenous, GPI-anchored TFPI-1 controls TF procoagulant activity in these cell types. [18][19][20][21][22][23] TNF-␣-stimulated HUVECs show increased ERK1/2 phosphorylation when triggered with a stabilized ternary TF-VIIa-Xa complex using the nematode inhibitor NAPc2. 9 We had also used mRNA expression levels of the TR3 orphan receptor gene, which has been demonstrated in endothelial cells of atherosclerotic lesions in vivo, 37 as an additional, potentially relevant readout for TFdependent signaling.…”
Section: Regulation Of Tf Signaling By Endogenous and Recombinant Tfpmentioning
confidence: 99%
“…12,14,15 Endogenous TFPI-1 is directly or indirectly anchored by glycosylphosphatidylinositol (GPI) on cell surfaces. [17][18][19][20][21][22][23] Lipoprotein receptor-related protein (LRP) and heparan sulfate proteoglycan (HSPG) have been implicated in the binding and internalization of recombinant forms of TFPI-1, depending on their C-terminal polybasic portions. 24,25 Endothelial cells, which are normally deficient in LRP, may bind TFPI-1 via HSPG and the very-low-density lipoprotein receptor.…”
Section: Introductionmentioning
confidence: 99%